PERSEPSI GURU DAN SISWA TERHADAP PEMBELAJARAN BERBASIS PROYEK DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS SISWA DI SEKOLAH DASAR - Nailah Abid Rahmadhani; Sabilla Sekar Ayu; Rahmawati Eka Saputri (STKIP Subang, 2025)
The results of this study show that from the teachers' perspective, PjBL has great potential to develop students' critical thinking skills, especially because it requires active involvement and problem solving. This method requires activity in the classroom, both from teachers and students. Teachers need to design projects that are contextual, challenging, yet still appropriate for the cognitive development level of elementary school students. However, from the students' perspective, this method is considered much more enjoyable than traditional instruction. However, in PjBL learning, some students find it difficult to understand. According to them, learning through projects makes them feel bored more quickly. Students require practice and guidance to become accustomed to independent and collaborative learning. Therefore, the success of PjBL implementation heavily depends on the teacher's active role in explaining it and designing a balanced learning strategy between exploration and direct guidance.